The Role Of Cross-Cultural Understanding in Interpreting English Recount Texts - Sya'roni, Roni; Hidayat, Didin Nuruddin (Department of English Language Education, UIN Sunan Ampel Surabaya, 2020)
This study aimed at analyzing the role of cross-cultural understanding in interpreting English recount texts. The data of this study were obtained by reviewing documents of a book entitled “Histories of Nations: How their identities were forged” (Furtado, 2017). As a qualitative content analysis, all the data were analyzed qualitatively by classifying, coding and interpreting the data gathered that led us to some conclusions and suggestions. The study found that there were some words and phrases in the recount text that requires cross cultural understanding in order to be able to interpret those texts accurately. Therefore, in interpreting the recount text, it is necessary to understand not only the text in literal meaning, but also the cultural context in a comprehensive way. This focuses on cultural context deals with the history of social organization and religion system. Cross cultural understanding eases the readers to interpret the recount text appropriately. The study suggests that cross cultural understanding should be an important topic to be learnt intensively in learning English language at least at university education level as it will enable students to be capable of understanding English discourses comprehensively.